Considerations Regarding Anesthesia for Renal Transplantation - Juni Kurniawaty; Cornelia Ancilla; Novita Intan Arovah (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2025)
Background : Transplantation provides near-normal life and excellent rehabilitation compared to dialysis and is the preferred method of treating end-stage renal disease (ESRD) patients.Methods: We conducted a retrospective analysis of anesthesia management from 20 cases of live renal transplants carried out between August 2017 and April 2019 at Dr. Sardjito Central General Hospital, Yogyakarta. Preoperative patient status, anesthesia management, and postoperative care of the subjects were assessed.Result : Most patients had preoperative anemia, normal serum potassium, normal serum creatinine, and normal ejection fraction. Anesthesia management began since 24 hours before surgery, in which the patients were hospitalized, had peripheral IV access and fluid maintenance, and hemodialysis, followed by premedication 1 hour before surgery. Prior surgery, anesthesia induction and intubation were done, followed by maintenance of anesthesia and intaoperative monitoring. Postoperative care consisted of administration of analgesia and management of complications.Conclusion: Optimization of preoperative status, proper anesthesia management, and good postoperative care are keys for a successful renal transplant program.